The Influences of Consumer Preference Characteristics towards Green Product: A Case of Naturemill Bin - Mustafa, S.K.; Musa, H.; Abdullah, A.R.; Azmi, F.R. (International Journal of Human and Technology Interaction (IJHaTI), 2017)
Despite a widespread adoption of green technology reported in many scholars, we continue to witness disappointing performance outcomes from their implementation. This can be explained largely by the failure of many studies to translate the initial adoption decision, made at an individual-level acceptance of a technology to be used by human. This study examines the key antecedents of the Technology Acceptance Model for users expected to use a naturemill bins in their day-to-day activities. In this study, we apply and extend the Technology Acceptance Model (TAM) to examine factors that influence acceptance of naturemill bins by individual users. Our focus is on the potential role of user-perceived naturemill bins quality dimensions as antecedents to the TAM’s cognitive mechanisms of perceived usefulness and perceived ease of use (PEU), and the user’s trust in using it. Our results confirm the core TAM relationships within the naturemill bins context and (PEU) found to be the most significant influencer of the consumer acceptance towards green products (Naturemill bin).